Pembibitan Tanaman Herbal melalui Model Home Herbal Medicine Garden untuk Mendukung Kemandirian Kesehatan Masyarakat: Herbal Plant Seedling through the Home Herbal Medicine Garden Model to Support Community Health Independence - Yasir, Muhammad; Setiawan, Jefri; Makole, Nurintan; Akbar, Faridun Taufik Muhammmad; Adrian, Muhammmad Fais; Hilda, Hilda; Embe, Wa; Asriani, Asriani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The program, Herbal Plant Seedling through the Home Herbal Medicine Garden Model to Support Community Health Independence, was implemented in Mataiwoi Village to enhance community knowledge and skills in cultivating herbal plants as a source of traditional family medicine. This program was designed as part of the PPK Ormawa initiative by HIMATIP, Muhammadiyah University of Kendari, through careful planning and collaboration with local stakeholders. A total of 20 participants, including PKK women’s groups and residents, took part in the program. The implementation methods included coordination with strategic partners (village governments, the PKK, and community health centers), training sessions on herbal plant seedlings, and field mentoring. Three types of herbal plants were cultivated during the program: ginger (Zingiber officinale), turmeric (Curcuma longa), and lemongrass (Cymbopogon citratus). The results showed a significant increase in participants’ knowledge regarding herbal seedling techniques, from 55% before training to 95% after. Beyond technical skills, the program fostered collective awareness of the importance of local resource-based health self-reliance. The Home Herbal Medicine Garden model proved effective as a community empowerment strategy and has strong potential for replication in other areas to support the achievement of the Asta Cita vision of community health independence.